Effect of Cartoon Shows on Kids Fashion - Brishti Panna2, Shikha Gupta1 , (International Journal of Scientific Research and Management (IJSRM), 2015)
It is not necessary to say that how much the children are interested in watching cartoon and shows on T.V. Actually watchingT.V. is not bad as we are living in the world of information and Technology .The Television programs are not the only reason for brighterand more empathetic generations but it is a good start. It is said that the children are being enriched in school as well as at home in front iftheir T.V. is an important step to making strong ,smart, caring and innovative future adults.We can easily notice the children watching Tomand Jerry, Loony Toons ,Dore-Mon, Sinchan, etc. on T.V.. Cartoons have changed drastically over the years and have lasting effects onchildren. Typically, children begin watching cartoons on television at an early age of six months, and by the age of two or three childrenbecome enthusiastic viewers. This paper will discuss the impact of these cartoon characters on the kids clothing behavior and will also tryto explore the reasons as to why the generation is more inclined towards television and these characters